Normal Hemoglobin Values in 12-24 Month Old Children - Zahedi Affandi; Harry Respati; Ponpon Ijradinata (Paediatrica Indonesiana, 1995)
One hundred and thirty-one children aged 12 to 24 months attending the Under Five Clinic of The Department of Child Health, Medical School, Padjadjaran University/Hasan Sadikin General Hospital in Bandung were studied. These subjects were "healthy" and they had no laboratory evidence neither of folic acid, vitamin B12 or iron deficiency, nor thalassemia minor, and/or hemoglobinopathy. These individuals were considered adequately nourished from the erithropoietic point of view, and they constituted the "normal" subjects from which values of hemoglobin were calculated. Results from this highly selected subjects indicated that the mean hemoglobin value was 127.2 g/L (range: 111.6-142.8 g/L). The lower limit of the hemoglobin value in this study is within the normal range according to the WHO criteria for normal hemoglobin values in children 6 months to 6 years of age.